PENGARUH PENGGUNAAN PENDEKATAN REBT DALAM KONSELING KELOMPOK TERHADAP HEDONISME SISWA KELAS XI MIA 1 PUTRI SMA MUHAMMADIYAH 10 SURABAYA - ayu nevanda, aulia sabrina; Mudhar, Mudhar; Mufidah, Elia Firda (Jurnal Bimbingan dan Konseling Pandohop, 2023)
The existence of a school in the middle of the city adjacent to the free world makes the level of hedonism high. So that the formulation of the problem is there any effect of using the rebt approach in group counseling on the hedonism of students. This study aims to determine the effect of using the rebt approach in group counseling on the hedonism of class XI MIA students at SMA Muhammadiyah 10 Surabaya. In this study, a pre-experimental quantitative approach was used in the form of a one-group pre-test post-test design. The population of this research is the students of class XI MIA 1 PUTRI SMAM X Surabaya, with a sample of 8 students of class XI who have a high level of hedonism. The samples were taken through purposive sampling technique with the hedonism scale data collection method. The data analysis method is used by non-parametric statistical analysis using the Wilcoxon test. The level of hedonism of students before being treated in the form of group counseling services with the rebt approach was in the high category with an average score of 85 then after being treated the group counseling service with the rebt approach was in the medium category with an average score of 64. The results of interpretation using the wilcoxon test can be seen Asymp.Sig (2-tailed) is worth 0.012. Where the value of 0.012 is smaller than <0.05, it can be concluded that there is a significant effect of group counseling services with a rebt approach on the hedonism of class XI MIA 1 Putri SMA Muhammadiyah 10 Surabaya.